Synthesis and Optimization of Snake Fruit Peel Ash-Derived Silica for Iron (Fe) Removal from Batik Wastewater - Siti Salamah; Ilham Mufandi; Jumiati Jumiati; Ainun Fadhilah (School of Postgraduate Studies, Diponegoro Univer, 2025)
The byproduct of the batik industry is a liquid waste containing heavy metals like iron (Fe) which can be harmful to the environment and aquatic ecosystems. The aim of this study is to synthesize and optimize silica derived from snake fruit peel ash as an adsorbent for iron (Fe) in the liquid waste of the batik industry. Snake fruit peel is often overlooked as waste and is identified to have a high silica content. The research method was carried out in the calcination process at a temperature of 650°C for 1 hour to convert and change the snake fruit peel powder into ash, then extracted using a 2M HCl solution. The final stage of silica synthesis is drying and grinding. The Silica characterization was analyzed using the FTIR (Fourier Transform Infrared Spectroscopy) and Surface Area Analyzer (SAA) tests. The metal content in the waste was analyzed with AAS (Atomic Absorption Spectrometer). The results showed that the silica from snake fruit peel ash contains silica constituent groups, namely silanol (Si-OH), as an active site for the adsorption process. The surface area of the silica is around 56.347 m2/g, the total pore volume is about 0.0193 cc/g, and the average pore diameter is approximately 26.6745 mm. The application test on batik liquid waste showed a decrease in Fe concentration from 0.487 mg/L to 0.343 mg/L at contact time of 60 minutes. This research proves that silica from snake fruit peel ash offers an innovative and sustainable solution for the treatment of batik industry liquid waste and in other liquid waste processing.